Awareness regarding reproductive health among young adults at a higher secondary school in Lalitpur - Parajuli, Puspa; Paudel, Narayani; Shrestha, Santoshi (Journal of Kathmandu Medical College, 2018)
Background: Reproductive health is a crucial feature of healthy human development and of general health. It may be a reflection of a healthy childhood, is crucial during adolescence, and sets the stage for health in adulthood and beyond the reproductive years for both men and women. Awareness of reproductive health among young boys and girls affects their health status, fertility and sets stage for health beyond reproductive years and affects the health of the next generation. Objectives: The objective of this study was to assess the awareness regarding reproductive health among young adults at a Higher Secondary school. Methodology: A descriptive cross-sectional study was conducted in one of the government higher secondary schools located at Karyabinayak municipality Lalitpur, Nepal. A total of one hundred and thirty eight students were selected purposively for the study. Data was collected through self administered questionnaire and data analysis was done by using Statistical Package for Social Sciences (SPSS) version 20. Results: Among 138 respondents, majority of the respondents (66.7%) had given the correct response regarding reproductive health. 76.8% knew that family planning is one of the components of reproductive health and 55.1% were aware of the legal age for marriage. Overall median percentage knowledge was 51.92 with range 17-78. Statistically significant association was found between level of knowledge and religion as well as respondents’ mother’s occupation (P< 0.05). Conclusion: On the basis of the findings of this study, it can be concluded that a majority of respondents were satisfactorily aware about reproductive health in superficial way, but in general, they had poor to average level of awareness regarding reproductive health.